Percutaneous osseointegrated prosthetic implant system - Jeyapalina Sujee; Beck James Peter; Holt Brian Mueller; Bloebaum Roy; Bachus Kent N (2017)
An implant system for securing a prosthesis to a selected bone of a subject including a stem and an abutment. The stem includes a porous region that promotes osseointegration of the selected bone following implantation of the stem. The abutment is secured to the stem and is configured for secure attachment to the prosthesis. The stem and the abutment include ultra-low friction and/or highly polished surfaces at select locations that inhibit bio-adhesion.